Tandospirone prevents stress-induced anxiety-like behavior and visceral hypersensitivity by suppressing theta oscillation enhancement via 5-HT1A receptors in the anterior cingulate cortex in rats - Zhan, Ting-Ting; Dong, Zhi-Yu; Yi, Li-Sha; Zhang, Yan; Sun, Hui-Hui; Zhang, Hai-Qin; Wang, Jun-Wen; Chen, Ying; Huang, Ying; Xu, Shu-Chang (Frontiers in Cellular Neuroscience, 2022)
Tandospirone, a third-generation of antianxiety agent with fewer side effects, has been widely used in the treatment of anxiety. Moreover, it is interesting that tandospirone has been found to relieve gastrointestinal symptoms in patients with refractory irritable bowel syndrome who also have psychological dysfunctions. However, the underlying mechanism remains unclear. In this study, using a visceral hypersensitivity rat model induced by chronic water avoidance stress to mimic the symptoms of irritable bowel syndrome, we found that tandospirone relieved anxiety-like behavior and visceral hypersensitivity induced by stress. Meanwhile, stressed rats had increased 5-HT concentration, less 5-HT1A receptor expression, and enhanced theta oscillations in the anterior cingulate cortex (ACC). Furthermore, the power of the theta band in ACC is positively correlated with the level of visceral sensitivity. Activation of 5-HT1A receptors by its agonist, 8-OH-DPAT, to compensate for their effect in ACC reduced the enhancement of theta oscillations in ACC slices in stressed rats, whereas 5-HT1A receptor antagonist, WAY100135, facilitates theta oscillations in slices of normal rats. Tandospirone reduced the enhancement of theta band power in ACC in vitro and in vivo, thus alleviating anxiety-like behavior and visceral hypersensitivity through 5-HT1A receptors in stressed rats. These results suggest a novel mechanism by which tandospirone activates 5-HT1A receptors to relieve stress-induced anxiety and visceral hypersensitivity by suppressing theta oscillation enhancement in ACC.